Biogenic synthesis of silver nanoparticles using nicotiana tobaccum leaf extract and study of their antibacterial effect - Prasad, Kumar Suranjit; Pathak, Darshit; Patel, Ankita; Dalwadi, Palak; Prasad, Ram; Patel, Pradip; Selvaraj, Kaliaperumal (African Journal of Biotechnology, 2011)
A green synthesis of silver nanoparticle was carried out using tobacco leaf extract. Synthesized nanoparticles were characterized using UV-Vis absorption spectroscopy, TEM, EDAX, FT-IR and photoluminescence study, respectively. UV-Vis absorption spectroscopy of prepared silver colloidal solution showed absorption maxima at 418 nm. Excitation maximum and emission maximum obtained from photoluminescence study were found at 414 and 576 nm, respectively. TEM analysis showed average particle size of 8 nm, while SAED pattern confirmed the crystalline nature of synthesized nanoparticles. FT-IR analysis indicated the involvement of carboxyl (-C = O), hydroxyl (-OH) and amine (-NH) functional groups of tobacco leaf extract in preparation of silver nanoparticles. EDAX analysis showed proportion of silver (54.55%) among other elements in nanoparticle. Pseudomonas aeruginosa and Escherichia coli DH5 alpha showed highest sensitivity towards silver nanoparticles.
Keywords: FT-IR spectroscopy; photoluminescence; silver nanoparticles; Tobacco; UV-Vis absorption

Defluoridation using biomimetically synthesized nano zirconium chitosan composite: kinetic and equilibrium studies - Prasad, Kumar Suranjit; Amin, Yesha; Selvaraj, Kaliaperumal (Journal of Hazardous Materials, 2014)
{The present study reports a novel approach for synthesis of Zr nanoparticles using aqueous extract of Aloe vera. Resulting nanoparticles were embedded into chitosan biopolymer and termed as CNZr composite. The composite was subjected to detailed adsorption studies for removal of fluoride from aqueous solution. The synthesized Zr nanoparticles showed UV-vis absorption peak at 420 nm. TEM result showed the formation of polydispersed, nanoparticles ranging from 18 nm to 42 nm. SAED and XRD analysis suggested an fcc (face centered cubic) Zr crystallites. EDAX analysis suggested that Zr was an integral component of synthesized nanoparticles. FT-IR study indicated that functional group like -NH
Keywords: Aloe vera; Chitosan; FT-IR spectroscopy; Sorption; Zirconium nanoparticles